Katyń Anniversaries in 1990–2010. The Position and Functions of Political Ritual in the Polish Culture of Remembrance. Research Report - Czubaj-Kuźmin, Sylwia (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2020)
The main goal of the research is to show the functional dimension of the political rituals associated with the celebrations of the Katyń massacre anniversaries in 1990-2010. Using the method of political linguistics, the study makes it possible to identify ten topoi organizing the Katyń anniversary discourse. They include the topos of “an innocent victim”, “violated justice”, “compensation”, “fair Russians”, “friends Muscovites”, “elite”, as well as the topos of “a shared field of remembrance, reconciliation” (“from foes to friends”), the topos of mutual forgiveness and the anniversary as a special occasion, or the topos of “inhuman land”. The pragmatic-semantic analysis of the contents of media reports accompanying the Katyń celebrations allows the author to show a number of functions that the Katyń ritual performed in the Polish culture of remembrance in 1990–2010. The study of functions proceeds from emotional, through normative, legitimization, integration and educational functions, to the performative function.

Głównym celem tekstu jest ukazanie funkcjonalnego wymiaru rytuałów politycznych związanych z obchodami rocznic zbrodni katyńskiej w latach 1990–2010. Dzięki przeprowadzonej metodą semantyczno-pragmatyczną analizie zawartości treści doniesień medialnych towarzyszących obchodom katyńskim, omówione zostały funkcje, które pełnił rytuał katyński w polskiej kulturze pamięci od 1990 do 2010 roku, takie jak funkcja emocjonalna, normatywna, legitymizacyjna, integracyjna, edukacyjna czy performatywna. Ponadto zaaplikowanie teorii traumy kulturowej umożliwiło analizę mitu założycielskiego, wskazywanego przez polityków w trakcie przemówień rocznicowych, wiążącego się z kłamstwem i prawdą o zbrodni katyńskiej. Zauważony w narracji katyńskiej przymus powtarzania, dotyczący walki z zakłamywaniem historii, odniesiony został do traumy spowodowanej damnatio memoriae, związanej z początkami chrześcijaństwa. W kontekście tych spostrzeżeń, w ramach rozważań na temat funkcji performatywnej, przeanalizowane zostało, obecne w dyskursie rocznicowym po katastrofie prezydenckiego samolotu lecącego na obchody 70. rocznicy zbrodni, zjawisko znane jako „drugi Katyń”.
Rocznice katyńskie w latach 1990–2010. Miejsce i funkcje rytuału politycznego w polskiej kulturze pamięci. Komunikat z badań
Keywords: political ritual; anniversary rhetoric; political linguistics; Katyń massacre crime anniversary; rytuał polityczny; retoryka rocznicowa; politolingwistyka; rocznica zbrodni katyńskiej